The Wind Turbine Design and Test - Paranchis, Mark Irwin; Pratama, Hendri (Teknomekanik, 2022)
Green energy harvester, known as wind turbine, able to convert mechanical works to electrical power. There are two main type of wind turbine that considered thoroughly, which are the horizontal and vertical axis wind turbine respectively. This project mainly focus on the design of new wind turbine that can operate well together in low wind speed condition in Malaysia. For the first stage of this project, the problems, purpose, and planning regarding with the project properly determined. Literature survey then furthered analyzed in order to know the wind power or behavior across the world, and specifically in Malaysia, research of turbine that can work in low wind speed condition, as well as parameter that often used in designing wind turbine by previous researcher. From the literature survey, the selected turbine was a Three-Bladed Savonius Wind Turbine, which is one type of Vertical Axis Wind Turbine (VAWT). That turbine will be attached to another VAWT turbine system to help generate more power and better performance. Design theoretical calculation and material selection have been properly analyzed before fabrication can be done. Upon completion of the fabrication, Savonius wind turbine section properly tested through experimental works by using simple wind tunnel in Faculty of Engineering Mechanical Workshop, and all readings and data collected using applicable tools and equipment. For the experimental works of Savonius rotor, the variable includes of blades curve angle from its center at different wind speeds. The data collected then interpreted through charts and graph for comparison and performance analysis, and conclude that 1200 blades curve angle from its center was the best among the other type of blades. From this project, it can be concluded that this type of mix wind turbine able to works in low wind speed condition in Malaysia, but a better improvisation and modification of the mix wind turbine will certainly improve its further performance and efficiency.